Cooling of motorcyclist helmet with thermoelectric module - Hrairi, Meftah; Abdullah, Abdullah F.; Ahmed, Mirghani Ishak (IDOSI Publications, 2013)
This paper deals with the development of cooling system for motorcycle helmet using thermoelectric technology. The system consists mainly of a heat sink and thermoelectric module. When electrical voltage is applied to the thermoelectric module, it will create a temperature difference across the thermoelectric module. This phenomenon is also known as Peltier effect, is being used to utilize electricity to pump heat. The prototype had been fabricated and mounted onto a motorcycle helmet. The designed thermoelectric cooled helmet was simulated using the finite element software ANSYS as well as experimentally tested for the cooling purpose. Experiments are conducted on the prototype to analyze the performance of the cooling system. The numerical and experimental results showed a good agreement and indicated that the temperature inside the helmet was reduced from 25.5°C to 19.3°C in approximately 6 min.